Nonleukoreduced red blood cell transfusion induces a sustained inhibition of neutrophil chemotaxis by stimulating in vivo production of transforming growth factor-β1 by neutrophils: role of the immunoglobulinlike transcript 1, sFasL, and sHLA-I - Ottonello, Luciano; Ghio, Massimo; Contini, Paola; Bertolotto, Maria; Bianchi, Giordano; Montecucco, Fabrizio; Colonna, Marco; Mazzei, Clemente; Dallegri, Franco; Indiveri, Franco (Transfusion (Philadelphia, Pa.), 2007)
BACKGROUND: Red blood cell (RBC) transfusion has been linked to increased susceptibility to infections in critically ill patients and to augmented incidence of postoperative infections. The mechanisms by which transfusions can induce immunosuppression are only partially defined. Recently, it has been demonstrated that RBC supernatants inhibit neutrophil migration. Such inhibitory activity is due to transforming growth factor (TGF)‐β1 contained in the supernatants that desensitize neutrophils to subsequent chemotaxic stimulation. STUDY DESIGN AND METHODS: In ancillary experiments, it was observed that plasma from transfused patients maintained its capacity of inhibiting neutrophil chemotaxis several days after RBC transfusion. Thus, this study was planned to investigate the mechanism(s) responsible for the prolonged inhibition of neutrophil chemotaxis observed after RBC transfusion. RESULTS: Plasma samples obtained from subjects who underwent RBC transfusion display a capability of inhibiting neutrophil chemotaxis, which is detectable up to 15 days after the transfusion. The inhibition is related to the capacity of FasL and HLA‐I molecules contained in RBC supernatants to induce in vivo TGF‐β1 synthesis by neutrophils. The induction of TGF‐β1 secretion in neutrophils by HLA‐I molecules depends on immunoglobulinlike transcript 1/CD85 triggering. CONCLUSION: The property of RBC transfusion of inducing a sustained inhibition of neutrophil chemotaxis seems to be a potential mechanism that concurs to the susceptibility to infections in patients who receive transfusions. Furthermore, our findings, showing neutrophil production of TGF‐β1 in response to FasL and HLA‐I molecules, confirm that neutrophils are endowed not only with effector functions but also with immunomodulatory properties possibly involved in the regulation of inflammatory processes.